Horizontal Transfer of Plasmid Mediated Carbapenem Resistant Genes from Klebsiella pneumoniae to Escherichia coli (Molecular Medicine Communications, 2022)
Carbapenem resistance among Enterobacteriaceae is an emerging problem worldwide. Klebsiella pneumonia carbapenemase (blaKPC) enzymes are amongst the most common beta-lactamases that have been studied. This broad group of organisms with various resistance mechanisms is associated with increased lengths of hospitalization, costs of medical care, morbidity, and mortality. The global spread of Carbapenem Resistance Enterobacteriaceae (CRE) has largely been attributed to disseminating a dominant strain of Klebsiella pneumoniae producing a serine beta-lactamase, termed as Klebsiella pneumonia carbapenemase (KPC). This study was designed to determine in vitro efficacy of horizontal transfer of plasmid-mediated carbapenem-resistant genes from Klebsiella pneumoniae to Escherichia coli. A total of 30 gram-negative rods from different clinical samples were taken. After preliminary antimicrobial susceptibility screening, isolates that showed a resistance zone were included in the study. These isolates were then subjected to the Modified Hodge test for confirmation of carbapenemase production. Out of 10 isolates, four were positive for carbapenemase production. The plasmid from these resistant strains was transformed into DH5α. RFLP analysis was carried to evaluate these transgenic cells resulted in horizontal gene transfer of resistant plasmid DNA from Klebsiella pneumoniae to Escherichia coli.
Keywords: Klebsiella pneumonia, Carbapenemase, Antimicrobial